1994
DOI: 10.1177/090756829400200302
|View full text |Cite
|
Sign up to set email alerts
|

Children solve problems: impact of an intervention programme on the problem-solving abilities of socially deprived children

Abstract: A sample consisting of 60 subjects from socially deprived environment were matched for age, gender, problem-solving ability and prolonged social deprivation score. This sample was further divided into an Experimental and a Control group, each consisting of 30 subjects. Pretesting of these subjects was done by administering three problem-solving tasks. A 16-week intervention programme was administered to the Experimental group to study its impact on the problem solving abilities of children whereas, the Control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Such interventions need to be designed with the target educational environments in mind (Verma and Verma, 1994 ; McKay et al, 1978 ). Cybersecurity books have been found to frequently contain outdated or incorrect information (Renaud & Prior, 2021a ).…”
Section: Discussion and Reflectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such interventions need to be designed with the target educational environments in mind (Verma and Verma, 1994 ; McKay et al, 1978 ). Cybersecurity books have been found to frequently contain outdated or incorrect information (Renaud & Prior, 2021a ).…”
Section: Discussion and Reflectionmentioning
confidence: 99%
“…While there is much evidence to suggest that living in financial deprivation has a negative impact on children’s educational attainment and health outcomes, there is also research to suggest that early interventions can effect positive changes. Interventions have been shown to have a positive impact in a variety of different areas including health (Freeman et al, 2016 ; Kaufman-Shriqui et al, 2016 ) language (Dobinson and Dockrell, 2021 ) and problem solving skills (Verma & Verma, 1994 ). McKay et al ( 1978 ) found that not only did early interventions improve educational outcomes, but that the earlier the intervention, the bigger the impact.…”
Section: Financial Deprivationmentioning
confidence: 99%
“…Fairytales could be used to illustrate and symbolize concepts that are now scientifically investigated by research on positive psychology, such as creativity, resilience, self-realization, problem solving, and personal growth (Verma & Verma, 1994; Vallerand, 2012; Weiss et al, 2016). Fairytales and narratives may serve as an action metaphor for helping individuals to better deal with their mixed emotions and developmental challenges, showing and teaching them more useful and positive coping strategies for conflict resolution (Ansell, 2016; Hill, 1992; Hohti & Karlsson, 2014).…”
mentioning
confidence: 99%
“…It improved children's eudaimonic well-being and reduced their somatic symptoms (Albieri et al, 2009;Ruini et al, 2015). Thus, various authors underlined the need to promote well-being in young populations and suggested to make education for well-being an integral part of the school curriculum (Baraldi, 2008;Glenn et al, 2013;Verma & Verma, 1994;Veronese & Castiglioni, 2015;Ruini et al, 2009;Proctor et al, 2011;Pluskota, 2014;Shoshani et al, 2014;Shoshani et al, 2016). However, excluding these preliminary studies, the existing literature gave only limited attention to eudaimonic or existential wellbeing (as opposed to happiness and hedonic well-being) in early stage of development (Ruini et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation